2021
DOI: 10.1093/cercor/bhab255
|View full text |Cite
|
Sign up to set email alerts
|

Communicative And Affective Components in Processing Auditory Vitality Forms: An fMRI Study

Abstract: In previous studies on auditory vitality forms, we found that listening to action verbs pronounced gently or rudely, produced, relative to a neutral robotic voice, activation of the dorso-central insula. One might wonder whether this insular activation depends on the conjunction of action verbs and auditory vitality forms, or whether auditory vitality forms are sufficient per se to activate the insula. To solve this issue, we presented words not related to actions such as concrete nouns (e.g.,“ball”), pronounc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Vitality forms convey an agent's internal states and thus play a crucial role in social interactions. In the last few years, several fMRI studies have been carried out to identify the neural substrate of vitality The middle cingulate cortex and dorso-central insula: A mirror circuit encoding observation and execution of vitality forms forms (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). These studies have shown that the dorso-central sector of the insula is the region that is selectively active in both the perception and expression of vitality forms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitality forms convey an agent's internal states and thus play a crucial role in social interactions. In the last few years, several fMRI studies have been carried out to identify the neural substrate of vitality The middle cingulate cortex and dorso-central insula: A mirror circuit encoding observation and execution of vitality forms forms (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). These studies have shown that the dorso-central sector of the insula is the region that is selectively active in both the perception and expression of vitality forms.…”
Section: Discussionmentioning
confidence: 99%
“…Refs. 5 12 confirmed the crucial role of this insula in encoding vitality forms. In a subsequent fMRI study, however, the same authors found that the cingulate cortex might also be involved in the encoding of vitality forms ( 7 ).…”
mentioning
confidence: 99%
“…It is possible to comprehend how the other person feels, directly, by hearing the tone contours of their voice regardless of verbal information. In one study specifically related to auditory vitality forms, Di Cesare et al (2022) imply that communicative intention is a necessary condition for processing one of the candidates of neural bases of vitality forms, that is, dorso-central insula (DCI).…”
Section: Introductionmentioning
confidence: 99%